Functional and evolutionary consequences of cranial fenestration in birds. (1st May 2017) - Gussekloo, Sander W. S.; Berthaume, Michael A.; Pulaski, Daniel R.; Westbroek, Irene; Waarsing, Jan H.; Heinen, Robin; Grosse, Ian R.; Dumont, Elizabeth R.
Abstract: Ostrich‐like birds (Palaeognathae) show very little taxonomic diversity while their sister taxon (Neognathae) contains roughly 10, 000 species. The main anatomical differences between the two taxa are in the crania. Palaeognaths lack an element in the bill called the lateral bar that is present in both ancestral theropods and modern neognaths, and have thin zones in the bones of the bill, and robust bony elements on the ventral surface of their crania. Here we use a combination of modeling and developmental experiments to investigate the processes that might have led to these differences. Engineering‐based finite element analyses indicate that removing the lateral bars from a neognath increases mechanical stress in the upper bill and the ventral elements of the skull, regions that are either more robust or more flexible in palaeognaths. Surgically removing the lateral bar from neognath hatchlings led to similar changes. These results indicate that the lateral bar is load‐bearing and suggest that this function was transferred to other bony elements when it was lost in palaeognaths. It is possible that the loss of the load‐bearing lateral bar might have constrained diversification of skull morphology in palaeognaths and thus limited taxonomic diversity within the group.